k = 1 ∑ ∞ 4 2 k + 4 2 k ( 2 k + 1 ) ( 2 k + 2 ) ( 2 k + 3 ) ζ ( 2 k + 4 ) = A − D B π C
The above equation holds true for positive integers A , B , C and D , where B and D are coprime. Find A + B + C + D .
Notation : ζ ( ⋅ ) denotes the Riemann zeta function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great writeup explaining these ideas! Thanks for sharing what you have learnt.
Extremely well written. Thank you!
Log in to reply
Learnt this from Mark Hennings!
Log in to reply
He is the best!
Log in to reply
@Pi Han Goh – I doubt whether my solution is right. It has been more than 2 days and no one has solved it. Can you closely verify my solution?
Log in to reply
@Aditya Kumar – It's definitely correct. Just tag Mark Hennings and wait for about 5 minutes and you will see your number of solvers increases by 1.
I used a variant of the standard identity k = 1 ∑ ∞ ζ ( 2 k ) z 2 k = 2 1 ( 1 − π z cot π z ) to note that F ( z ) = k = 1 ∑ ∞ ζ ( 2 k + 4 ) z 2 k + 3 = 9 0 z 4 5 − 1 5 π 2 z 2 − π 4 z 4 − 4 5 π z cot π z and then calculate the sum as 4 5 1 F ′ ′ ′ ′ ( 4 1 ) = 1 2 − 1 2 8 5 π 5
I did it the same way except for a slight minor change that k = 1 ∑ ∞ ζ ( 2 k + 4 ) x 2 k + 4 = 2 1 − 2 π x cot ( π x ) − x 2 ζ ( 2 ) − x 4 ζ ( 4 )
Problem Loading...
Note Loading...
Set Loading...
For ∣ x ∣ > 1 , by geometric sum, we have: k = 1 ∑ ∞ x 2 k 1 = x 2 − 1 1 = 2 1 ( x − 1 1 − x + 1 1 )
On differentiating it 4 times, we get: k = 1 ∑ ∞ x 2 k + 4 2 k ( 2 k + 1 ) ( 2 k + 2 ) ( 2 k + 3 ) = 1 2 ( ( x − 1 ) 5 1 − ( x + 1 ) 5 1 )
Now, coming to our summation, we have: k = 1 ∑ ∞ 4 2 k + 4 2 k ( 2 k + 1 ) ( 2 k + 2 ) ( 2 k + 3 ) ζ ( 2 k + 4 ) = k = 1 ∑ ∞ j = 1 ∑ ∞ ( 4 j ) 2 k + 4 2 k ( 2 k + 1 ) ( 2 k + 2 ) ( 2 k + 3 ) = j = 1 ∑ ∞ k = 1 ∑ ∞ ( 4 j ) 2 k + 4 2 k ( 2 k + 1 ) ( 2 k + 2 ) ( 2 k + 3 ) = 1 2 j = 1 ∑ ∞ ( ( 4 j − 1 ) 5 1 − ( 4 j + 1 ) 5 1 ) = 1 2 n = 1 ∑ ∞ ( 2 n + 1 ) 5 ( − 1 ) n − 1 = − 1 2 n = 0 ∑ ∞ ( 2 n + 1 ) 5 ( − 1 ) n + 1 2
The sum we obtained is Dirichlet-Beta function, which is defined as: β ( s ) = n = 0 ∑ ∞ ( 2 n + 1 ) s ( − 1 ) n
We'll use the following recurrence formula to evaluate it: β ( 2 n + 1 ) = − k = 1 ∑ n ( 2 k ) ! ( − π 2 / 4 ) k β ( 2 n − 2 k + 1 ) .
Now we can simply evaluate β ( 1 ) = 4 π .
Now, we get β ( 5 ) = 1 5 3 6 5 π 5 .
Now, plugging it into our main summation, we get: k = 1 ∑ ∞ 4 ( 2 k + 4 ) 2 k ( 2 k + 1 ) ( 2 k + 2 ) ( 2 k + 3 ) ζ ( 2 k + 4 ) = 1 2 − 1 2 8 5 π 5
Here, A = 1 2 , B = 5 , C = 5 , D = 1 2 8 . Hence, A + B + C + D = 1 5 0